To free the captives : a plea for the American soul - Smith, Tracy K. (Alfred A. Knopf, 2023)
"From the Pulitzer Prize-winning poet: a stunning meditation on ritual and collectiveness that explores how older forms of inquiry-from song to prayer to ways of public gathering-might help us all survive violent times and address America's shared history"--